ANALISIS PELAKSANAAN PERJANJIAN JAMINAN FIDUSIA (Studi Kasus FIF Astra) (Ahkam: Jurnal Hukum Islam, 2019)
This research is to find out the process of implementing a fiduciary guarantee agreement and to know the legal consequences of a fiduciary guarantee agreement when FIF Astra is not registered. Based on the results of the study it can be concluded that in terms of its implementation and the contents of FIF Astra's financing agreement, it has fulfilled the provisions of legislation, especially the Civil Code. This is intended to provide legal certainty for the parties, both for fiduciary providers and for fiduciary recipients so that they can provide legal protection to creditors (fiduciary recipients) and other third parties. Regarding to the consequences of fiduciary guarantee law which is not registered according to Law Number 42 of 1999 that fiduciary guarantees must be made with a Notary Deed and registered with the Office of the Ministry of Law and Human Rights, in order to have execution power, in addition, creditors will obtain preferential rights. If the fiduciary guarantee is not made under the hand and is not registered in accordance with the provisions of the legislation, it does not have the execution power, and the right of preferential rights and can be nullified and voided by law.Keywords: Implementation of the agreement, Fiduciary Guarantee